Feasibility Comparative Analysis of Providing Earthquake Sensor Services and Video on Demand by Utilizing Frequency License 3.3 GHz and Bandwidth 12.5 MHz - Siti Hajar Komariah; Ananda Risya Triani; Rohmat Saedudin (Jurnal Rekayasa Sistem & Industri, 2022)
several companies. One of the license holders is a telecommunications company located in Bandung andJakarta. This 3.3 GHz frequency, in the map for the performance of 5G telecommunication services,includes candidates for the medium class working frequency which is predicted to be auctioned by thegovernment to become the working frequency for 5G performances. Several companies have an interest inidentifying the use of 3.3 GHz and 12.5 MHz BW licenses outside the stand-alone performance of 5Gtechnology-based broadband telecommunications services. Initial identification and studies show that thereare two services that have the potential to be deployed by utilizing the frequency range and BW, namelyearthquake sensor network services and Video on Demand (VoD) in DKI Jakarta. To ensure the feasibilityof performing these two services based on the technology owned by the telecommunications company,further studies are needed by analyzing them from the market aspect, technical aspect, and financial aspect.This research was conducted using a techno-economic approach and analysis. The novelty in this research is the implementation of new 5G technology licensed with 3.3 GHz frequency and 12.5 MHz bandwidth inthe new case, namely the earthquake sensor network compared to other services, namely video on demand.The next process is the comparison of the performance feasibility parameters (NPV, IRR, and PaybackPeriod) based on the results of a study of the two services that can be carried out to determine the priorityservice candidates to be provided by the telecommunications company. The results show that in terms ofoperational and financial aspects, the earthquake sensor project will be more profitable for the companybecause the effort spent is not too large.